2023
DOI: 10.3390/molecules28217433
|View full text |Cite
|
Sign up to set email alerts
|

Nocardioides: “Specialists” for Hard-to-Degrade Pollutants in the Environment

Yecheng Ma,
Jinxiu Wang,
Yang Liu
et al.

Abstract: Nocardioides, a genus belonging to Actinomycetes, can endure various low-nutrient conditions. It can degrade pollutants using multiple organic materials such as carbon and nitrogen sources. The characteristics and applications of Nocardioides are described in detail in this review, with emphasis on the degradation of several hard-to-degrade pollutants by using Nocardioides, including aromatic compounds, hydrocarbons, haloalkanes, nitrogen heterocycles, and polymeric polyesters. Nocardioides has unique advantag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(3 citation statements)
references
References 111 publications
1
2
0
Order By: Relevance
“…Analyses using FAPROTAX and KEGG suggested that the increased abundances of Nocardioides and Rhodococcus were responsible for the biodegradation and metabolism of xenobiotics, particularly aromatic compounds, by Cyps and other enzymes (Figure c,d). The results obtained align with prior research indicating that Nocardioides and Rhodococcus , both categorized within the bacterial taxon Actinobacteria, possess unique advantages in the effective degradation of recalcitrant pollutants. These findings reveal the participation of intestinal microbiota in 6PPDQ detoxification.…”
Section: Discussionsupporting
confidence: 86%
“…Analyses using FAPROTAX and KEGG suggested that the increased abundances of Nocardioides and Rhodococcus were responsible for the biodegradation and metabolism of xenobiotics, particularly aromatic compounds, by Cyps and other enzymes (Figure c,d). The results obtained align with prior research indicating that Nocardioides and Rhodococcus , both categorized within the bacterial taxon Actinobacteria, possess unique advantages in the effective degradation of recalcitrant pollutants. These findings reveal the participation of intestinal microbiota in 6PPDQ detoxification.…”
Section: Discussionsupporting
confidence: 86%
“…Actinobacteria are oleophilic organisms frequently found in petroleum-contaminated soils (Nocardia genu) [ 77 ]. Nocardioides has a significantly higher degradation rate than other PAH-degrading bacteria and needs less time to break down these compounds [ 78 ]. Anaeromyxobacteraceae (Mixococcia) is an unusual myxobacterial genus that has been described in a wide variety of habitats due to its bioactive spectrum and secondary metabolites [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of a large number of chemical pesticides, insecticides, fungicides, bactericides, and soil fumigants has a negative impact on soil, water resources, air, and human health ( Deng et al, 2019 ). It is reported that Blastococcus , Solirubrobacter , Gemmatimonas , among others, have the ability to degrade pesticides ( Du et al, 2022 ), while Nocardioides can withstand various low-nutrient conditions and concurrently degrade pollutants ( Ma et al, 2023 ). We observed that the relative abundances of Blastococcus, Nocardioides, Solirubrobacter , and Gemmatimonas in the rhizosphere soil samples of Akihime were significantly higher than those of F. nilgerrensis ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%